2008
DOI: 10.1111/j.1466-7657.2008.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Chinese undergraduate nursing students' perceptions of the nursing profession

Abstract: No correlations were found between nursing students' attitudes towards nursing and their demographic characteristics. Clinical experience apparently had no impact on nursing students' professional perception. However, the curriculum design appears to play an important role in forming the students' attitudes towards nursing. Significant implications and suggestions for nursing educators and nursing managers are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
3
19
0
3
Order By: Relevance
“…These transformations affect societal views of the nursing profession, as well as the perceptions of students who are influenced by social culture. The results of studies regarding student attitudes towards the nursing profession indicate that the changes observed in our country are similar to those reported worldwide (Zhang &Petrini 2008 ;Grainger &Bolan 2006).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…These transformations affect societal views of the nursing profession, as well as the perceptions of students who are influenced by social culture. The results of studies regarding student attitudes towards the nursing profession indicate that the changes observed in our country are similar to those reported worldwide (Zhang &Petrini 2008 ;Grainger &Bolan 2006).…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported that exposure to the clinical field during early stages of the nursing program is critical to perception of the nursing profession (Zhang &Petrini 2008 ;Nilsson & Silén 2010). The clinical learning field is the starting point for professional practices for nurses and contributes to the development of student views (Papathanasiou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [24,41] have also found that further study was one of the most frequently cited choices of nursing graduates. On the other hand, the fact that only a minority of the participants, plan to continue their career as staff nurses must be of concern and highlights the importance of structured nursing career clinical pathways.…”
Section: Cultural Influencesmentioning
confidence: 95%